OVERVIEW OF PLANNING AND UTILIZATION OF VILLAGE FUNDS IN THE HEALTH SECTOR IN REDUCING STUNTING IN ACEH JAYA DISTRIC - Lisma, Wida; Ertika, Yenny (Teunuleh Publisher, 2022)
Based on EPGBM data through SKPK Sekber Bangraja, aceh jaya stunting presentation data which is at 25.5%, this percentage is quite high with the total population and target children around 8000 children. To prevent and handle cases of stunting malnutrition in Aceh Jaya Regency, the first step of skpk Sekber Bangraja was carried out through the action of 1 stunting addiction. Prevention of stunting reduction in Aceh Jaya Regency is implemented through posyandu activities in each village with cooperation between village cadres, nutrition officers, village midwives and posyandu cadres. This study uses a qualitative descriptive method, with skunder data from the results of analyzing problems related to the effectiveness of preventing stunting reduction in Aceh Jaya district. The results of this study, in the implementation of stunting reduction are SKPK Sekber Bangraja and especially DPMPKB, Dinas Kesehatan, BPKK, Bappeda, Disdukcapil and Dinas Sosial, to prevent stunting reduction in Aceh Jaya Regency, therefore SKPK is involved in carrying out activities for the prevention and reduction of stunting in locus villages so that the integration among the SKPK involved can produce maximum output in accelerating the reduction of stunting rates.